EFFECT OF COMPUTER ASSISTED INSTRUCTION ON STUDENTS’ ACADEMIC ACHIEVEMENT AND RETENTION IN RADIO TELEVISION AND ELECTRONIC WORKS IN TECHNICAL COLLEGES IN LAGOS STATE (NAU Journal of Technology and Vocational Education, 2024)
The study investigated the effects of Computer- Assisted Instruction on students’ achievement and retention in Radio Television and Electronic Works in Technical Colleges in Lagos State. Two research questions and two research hypotheses guided the study. The study adopted quasi- experimental research design. The instrument used for data collection are Radio Television Electronic Works Assessment Sheet (RTVEWAS) and Retention Test on Radio Television and Electronic Works (RTRTVEW) developed for the study whose reliability obtained using Guttmann Split-Half Coefficient whose coefficient value was 0.805. And the sample of the study comprises of seventy- eight (68) students which was drawn from two Technical Colleges as follows: Government Technical College (GTC) Agidingbi (experimental group) – thirty (33) and Government Technical College (GTC) Adosoba (control group) –thirty- five (35) students. The data collected was analysed using mean and standard deviation in order to answer the research questions while ANCOVA was used to test the hypothesis. The research findings revealed that there was no significant difference between the academic achievement of students taught in RTVEW using drill and practice method and those taught using demonstration method in Technical colleges in Lagos State and there was no significant difference between the retention ability of students taught RTVEW using drill and practice method and those taught using demonstration method in Technical colleges in Lagos State.
Keywords: Technical College; RTVEW; Computer- assisted instruction; Achievement; Retention